LAND REGISTRATION ACCELERATION IN INDONESIA: A LESSON-LEARNED GUIDELINE FROM LAND REGISTRATION ISSUES IN MALAYSIA (UUM Journal of Legal Studies, 2022)
Every country has its land policy system. Indonesia employs deeds registration which refers to the Basic Agrarian Law (BAL) and Malaysia uses a title registration system called the National Land Code (NLC). Indonesia has yet to complete its land registration mandate throughout the country since the mandate was officially introduced in the BAL 1960. While Malaysia has adopted a Torrens system concerning land matters, recognising that land registration is everything. The first part of the paper focuses on beneficial ownership, confidential land ownership data, identifying land registration constraints and strengthening land administration abilities, while the second part focuses on land registration as a legal instrument and land rights ownership affirmation. The main question in this research is to analyse whether the quantity, quality and legal certainty guarantees of land registration are strongly influenced by a well-organised land registration system. Indonesia and Malaysiaare still addressing weaknesses in their respective land registration systems based on issues. There is a need for improvement of roles from two main stakeholders, namely the government’s role in streamlining administration and the role of community participation in supporting successful land registration. This paper will also provide recommendations for academicians, government/institutional leaders, and legislators to assess and continuously strengthen the BAL as the fundamental principle of land law in Indonesia, especially in its land registration system and legal certainty over land registration.